(untitled) (International Journal of Environmental Sciences, 2025)
Food is the basis of human survival and is crucial for maintaining physical as well as mental well being of an individual. Food adulteration is a global public health concern. And with time, it is turning into a menace especially with respect to children, women and other marginalized population. Due to the fact that consumption of adulterated food does not have imminent health effects on consumers, a large number of cases related to food adulteration go unnoticed and unreported. In India, the concerned laws have undergone amendments but food, instead of being a source of nutrition and wellness is becoming a source of ill-health to individuals. The issue of food adulteration in India raises a serious concern towards the inefficiencies in the legal system despite having the relevant laws in place. The paper proceeds on the premise that food safety is one of the fundamental public health concerns as adulterated food leads to various long-term illnesses like cancer, multiple organ damage, and can be fatal too. The paper seeks to highlight the economic impact of food adulteration which is, the increased health care cost on the consumers in the form of out-of- pocket expenses which is already high in India. The paper further seeks to identify cases of food adulteration in India and explore its impact on public health among the Indian population. The study further delves into evaluating the existing law related to food adulteration in India and to examine how effective the current legal framework in India is thereby evaluating the inefficiencies in implementation leading to degraded public health outcomes. Understanding the risks involved with the ill-effects of food adulteration would help in devising an efficient strategy to alleviate the adverse health consequences. The study also aims at making a cross-country analysis comparing food adulteration trends and regulations in developed and developing countries. The present paper is divided into five parts. The first part gives an overview of the issue of food adulteration at the domestic and global level and throws light on the effects on the healthcare sector. The second part deals with how food adulteration is a public health concern in India with special focus on the epidemiological studies across the country. The third part of the paper explains the existing Indian legal framework that covers the issue of food safety and the Laws criminalizing food adulteration in India. The fourth part delves into the role played by Food Safety Standards Association of India (FSSAI) and the Indian Judicial System in strengthening food safety. Part Five includes the conclusion and suggestions by the authors.